Prognostic value of HPV circulating tumor DNA detection and quantification in locally advanced cervical cancer - Beaussire-Trouvay, Ludivine; Duhamel, Orianne; Perdrix, Anne; Lévêque, Emilie; Vion, Roman; Rovelet-Lecrux, Anne; Sarafan-Vasseur, Nasrin; Di Fiore, Frédéric; Crouzet, Agathe; Leheurteur, Marianne; Clatot, Florian (Frontiers in Oncology, 2024)
Background Cervical cancers are mainly caused by an oncogenic HPV. For locally advanced stages, the standard treatment is radio-chemotherapy (RTCT) followed by brachytherapy. Nevertheless, the prognosis remains highly heterogeneous between patients. Objective We investigated the prognostic value of HPV circulating tumor DNA (ctDNA) in locally advanced cervical cancers alongside that of Squamous Cell Carcinoma Antigen (SCC-A). Methods This single-center retrospective study included patients treated in curative intent for an IB3 to IVA squamous cell cervical cancer. Quantification of HPV ctDNA in serum collected at diagnosis was performed using a multiplex digital PCR assay for the simultaneous detection of 8 HPV genotypes. Results Among the 97 patients included, 76 patients (78.4%) were treated by RTCT, followed by brachytherapy for 57 patients (60%). HPV ctDNA was detected in 59/97 patients at diagnosis (60.8%). This detection was associated with lymph node invasion (p=0.04) but not with tumor stage. A high level of SCC-A at diagnosis was associated with tumor stage (p=0.008) and lymph node invasion (p=0.012). In univariate analysis, better disease-free survival (DFS) was associated with optimal RTCT regimen (p=0.002), exposure to brachytherapy (p=0.0001) and a low SCC-A at diagnosis (continuous analysis, p=0.002). Exploratory analysis revealed that 3/3 patients (100%) whose HPV ctDNA was still detectable at the end of treatment relapsed, while 6/22 patients (27.3%) whose HPV ctDNA was negative at the end of treatment relapsed. Conclusion HPV ctDNA detection at diagnosis of locally advanced cervical squamous cell carcinomas is frequent and related to node invasion, but not to DFS. The prognostic value of HPV ctDNA detection after treatment warrants specific studies.